Impacts of Climate Change on Water Resources, Agricultural Production and Food Security: Evidence from Turkiye - Mozharul Islam (Journal of Economy Culture and Society)
Since agricultural production depends mainly on nature and uses surface and groundwater reservoirs, changes in existing water resources significantly affect this sector. Again, changes in global climate bring changes in water levels, consequently affecting agriculture, food supply, and income sources of households in different areas. However, to date, no such research has investigated the farmers who are the producers and the most vulnerable group to the impacts of climate change. Therefore, this paper explores climate change impacts on the water resources of Sarayonu, which in turn affects the agricultural food production and food security of the producers' households and the country's market. This qualitative study conducted in-depth interviews with the farmers from the Sarayonu district of Konya province in Turkiye. The study results show that ground and surface water resources are negatively affected by climate change. Consequently, the study area observed a decrease in water level over the last 15 years. Thus, these changes in water resources have been significantly affecting the agriculture sector, which alters the food supply for the market in general and the producers in particular. When people have less water, they have low quality and quantity crop yields, resulting in food crises and economic difficulties